Potential Traffic Accident Analysis of Bangkinang – Rantau Berangin Road Riau Province, Indonesia - Abdul Kudus Zaini; Abdussalam (Jurnal Inovasi Teknologi, 2021)
A traffic accident is an unexpected and unintentional event involving a vehicle with or without other road users, resulting in human casualties (minor injuries, serious injuries, and death) and property loss. In penel itian have taken vertebra way the segments road Bangkinang - Rantau Berangin KM 60 to KM 100 . This study aims for know se how much the level of traffic accidents in the area and for get The value of Accident Rate is Black Spot and Black Site on road Bangkinang-Rantau Berangin.The method used in this research is the Calculation Analysis method by identifying the Black Spot and Black Site based on the Accident Rate . The results of the analysis of data years 2014 - 2018 indicates that the segments road Bangkinang - Rantau Berangin can be identified value Accident rate which is Black Spot is the village of Pulau Gadang - Tanjung Alai with accident rate amounted to 2,069 and also the village of Tanjung Alai – Batu Bersurat with grades Accident rate amounted to 2,069. While for Accident rate against Black Site among others , namely the segment road Tanjung Alai – Batu Bersurat with Accident rate of 0.295 followed by the village of Pulau Gadang - Tanjung Alai is 0,258 and followed the village of Kuok - Village Lereng with Accident rate 0,240. From the analysis the researchers concluded that there are three locations which are the areas rawaan traffic accidents on roads Bangkinang - namely Rantau Berangin Village Tanjung Alai - Village Batu Bersurat , the village of Pulau Gadang - Tanjung Alai and villages Kuok - Village Lereng